2019
DOI: 10.1097/phm.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Intake Relative to Total Daily Energy Expenditure Using a Spinal Cord Injury–Specific Correction Factor

Abstract: Objective The aims of the study were to evaluate the influence of level of spinal cord injury (SCI) on caloric intake relative to total daily energy expenditure (TDEE) and body composition, and to develop a SCI–specific correction factor for the TDEE estimation. Design Individuals with paraplegia (PARA, n = 28) and tetraplegia (TETRA, n = 13) were analyzed. Daily caloric intake, basal metabolic rate, and TDEE were obtained using dietary recall, indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 26 publications
0
68
0
Order By: Relevance
“…We assessed 331 full texts, of which we identified 57 studies reporting on body composition according to the level of injury. Forty studies (40/57, 70.2%) [10,[13][14][15][16] could be quantitatively pooled (38 cross-sectional and 2 longitudinal analysis), which comprised 4872 individuals with SCI (Figure 1). Table 1 summarizes the study characteristics of quantitatively pooled studies, and the details of each study included in the systematic review can be found in Table S1.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We assessed 331 full texts, of which we identified 57 studies reporting on body composition according to the level of injury. Forty studies (40/57, 70.2%) [10,[13][14][15][16] could be quantitatively pooled (38 cross-sectional and 2 longitudinal analysis), which comprised 4872 individuals with SCI (Figure 1). Table 1 summarizes the study characteristics of quantitatively pooled studies, and the details of each study included in the systematic review can be found in Table S1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Seventeen studies (17/57, 29.8) [10,12,17,18,42,[66][67][68][69][70][71][72][73][74][75] were excluded from the analysis but were qualitatively reported (Table S2). The reasons for exclusion were: (i) seven studies failed to provide quantitative measure among different injury levels, (ii) seven studies were deemed to be similar reports of an included study, (iii) two studies cannot be pooled due to difference in reporting, and (iv) one study did not provide measures of spread (no standard deviation).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Persons with SCI have been reported to have reduced energy expenditure resulting from a marked reduction in lean tissue mass and in the ability to ambulate and/or exercise ( 39 , 40 ). On the other hand, recent reports indicated increased total food intake in persons with SCI when compared to individuals who were immobilized for reasons other than SCI ( 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%